Arming as a Strategic Investment in a Cooperative Equilibrium - Garfinkel, Michelle R. (American Economic Review, 1990)
To develop a positive, economic theory of military spending, the analysis focuses on a game-theoretic, general equilibrium model of international conflict, in which consumption, peaceful investment, and military spending are endogenously determined. The analysis illustrates that when there is repeated interaction between nations, a game of threats and punishments generally will not support a disarmament outcome and that fluctuations in military spending can be an endogenous result of fluctuations in aggregate economic activity. Furthermore, the analysis shows how the relation between aggregate economic activity and military spending qualitatively depends on whether governments are acting opportunistically or cooperatively.